Sorption and Desorption Phenomena of Urban Biowaste-Based Heavy Metals by a Ferralsol - Ntambi, Emmanuel; Tenywa, John Stephen; Ntale, Muhammad (Journal of Agricultural Chemistry and Environment, 2020)
Background: The objective of this study was to examine the adsorption-desorption phenomena of heavy metals in an agricultural Ferrosol treated with sewage solid waste at rates usually applied for soil fertility management. Methods: The study was carried out under laboratory conditions, using a Ferralsol sourced from Makerere University Agricultural Research Institute, Kabanyolo (MUARIK). Soil and sewage solid waste were analysed for pH, organic matter, cation exchange capacity and heavy metals (copper, zinc, chromium and lead). Soil was treated with sewage solid waste at input rates of 0, 50, 100, and 150 g per pot (equivalent to 0, 2.5, 5.0 and 7.5 metric tons∙ha−1 respectively); and supplemented with phosphorus. The phosphorus was applied At rates of 0, 0.795, 1.591 and 2.385 g per pot (equivalent to 0, 25, 50 and 75 kg∙ha−1, respectively). Batch adsorption was used to study the sorption- desorption of heavy metals on the treated soil and the Langmuir and Freundlich models were used to analyse the data. Results: Adsorption and Desorption isotherms fitted better to Freundlich equation than Langmuir model. Chromium was the most sorbed and retained metal; while lead was the least retained overall. The desorption process was virtually irreversible, considering the low amounts of the metals desorbed. Chromium fitted relatively better to both models than the copper, zinc and lead. All the four metals were less desorbed at high metal concentrations. Conclusion: The four metals would not be available at high metal concentrations especially when the application rate used is ≥ 5.0 tones∙ha−1 of the sewage solid waste. Thus, the metals would not be available for plant uptake and the chance to contaminate Groundwater is very limited especially for chromium.
Keywords: Heavy Metals; Sewage Solid Waste; Ferralsol; Sorption-Desorption